Towards sustainable green diesel fuel production: Advancements and opportunities in acid-base catalyzed H2-free deoxygenation process - Asikin-Mijan, N.; Juan, J.C.; Taufiq-Yap, Y.H.; Ong, Hwai Chyuan; Lin, Yu-Chuan; AbdulKareem-Alsultan, G.; Lee, H.V. (Elsevier B.V., 2023)
This review delves into the potential of renewable biomass for green diesel production. Deoxygenation technology offers a promising method for converting biomass-derived oxygenates oil into high-grade hydrocarbon factions. Hence, various deoxygenation pathways of biomass conversion under free‑hydrogen environment were explored. Additionally, the prospects of acid-base bifunctional catalysts to facilitate deoxygenation was discussed, highlighting the correlation between the physicochemical properties of the catalysts and catalytic activity. However, it should be noted that the acid-base characteristics of the catalysts contribute to the breaking of C–O bonds of oxygenated oil via undesirable pathways, which contributed to unfavorable by-product and catalyst deactivation.